Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis